Modern trends in chronic pain treatment with opioid analgetics - E. S. Vvedenskaya (Лечащий Врач, 2022)
The article notes the up-to-date problem of adequate chronic pain relief in patients with various diseases, indicates the concept’s weakness of using opioids as the main means for moderate to severe chronic pain control proposed by the WHO in 1986, emphasizes the importance of their use only as an adjunct to rational pathogenetic pain therapy – as a multimodal analgesia component – in both cancer and non-cancer patients. It gives the information on the possibility and features of narcotic analgesics minimal dosages use for moderate pain control. The innovative pharmacological class of drugs with a dual mechanism of action representative, an agonist of μ-opioid receptors and a norepinephrine reuptake inhibitor, tapentadol, is characterized. The mechanism of its action, advantages, efficacy and safety, place and features of its use in clinical practice are analyzed. In the department of palliative care of one of the city clinical hospitals in Nizhny Novgorod, long-acting tapentadol has been used since 2018. Over the past two years, more than 70% of patients suffering from chronic pain syndrome of moderate to severe intensity received it in the hospital. The drug is prescribed to patients with various forms of chronic pain syndrome in malignant neoplasms, for example, of the pancreas, stomach and intestines, involvement of the pleura and soft tissues in the pathological process, with bone pain. The starting dose is usually 50 mg twice a day, then it often rises with an increase in pain to 300-500 mg per day. The drug is used when tramadol is ineffective in a daily dose of 200-300 mg or when it is poorly tolerated by the patient. Of the side effects, in rare cases, there is the appearance of nausea and dizziness, in isolated cases, the appearance of drowsiness and mild cognitive impairment in debilitated patients. As a rule, these side effects disappear after a few days.